Analysis of the Accuracy Level of Revenue and the Distribution Mechanism of Tax Revenue Sharing and Non-Tax Revenue Sharing for the Jambi Province Government in 2015-2019 - Abdi Sukma; Bambang Niko Pasla; Fathiyah Fathiyah (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2021)
This study aims to analyze the accuracy of receipts and mechanisms for disbursement of Tax Revenue Sharing funds and Non-Tax Revenue Sharing of the Jambi provincial government in the fiscal year 2015 - 2019. Research is quantitative by using secondary data from the Jambi Provincial Government Budget Realization report for the Fiscal Year 2015 - 2019. Based on the results of the analysis can be concluded that the accuracy of receipts using the formula of efficiency calculation between the budget/target with the realization of balance funds dagi tax revenue sharing and Non-Tax Revenue Sharing in the five years in Jambi Province is inaccurate so as to cause the realization far exceeds or less than the budgeted revenue, and the distribution mechanism is also not on time and often late for reasons of miscalculation so that it must be recalculated, this will result in delays and even unenforceable project activities for regional development.